Characteristic cytokine profile of the aqueous humor in eyes with congenital cataract and pre-existing posterior capsule dysfunction - Zhao, Yinying; Zhao, Qihui; Zhang, Hongfang; Zhang, Zhewen; Wang, Dandan; Li, Zhangliang; Ding, Xixia; Zhao, Yune (Frontiers in Medicine, 2024)
Objectives: To investigate the characteristic cytokine profile of the aqueous humour in eyes with congenital cataract and pre-existing posterior capsule dysfunction (PCD).In this cross-sectional study, the enrolled eyes with congenital cataract and PCD were included in the PCD group, while those with an intact posterior capsule were included in the control group.Demographic data and biometric parameters were recorded. The levels of 17 inflammatory factors in the aqueous humour collected from the enrolled eyes were detected using Luminex xMAP technology, and intergroup differences in the collected data were analysed.The PCD group comprised 41 eyes from 31 patients with congenital cataract and PCD, whereas the control group comprised 42 eyes from 27 patients with congenital cataract and an intact posterior capsule. Lens thickness was significantly thinner in the PCD group than in the control group. However, the levels of monocyte chemoattractant protein-1 (MCP-1), transforming growth factor-β2 (TGF-β2), and vascular endothelial growth factor (VEGF) were significantly higher in the PCD group than in the control group. Multivariate logistic regression confirmed that lens thickness and TGF-β2 level were independent risk factors for PCD.A thinner lens thickness in eyes with congenital cataract and PCD could serve as a biometric feature of these eyes. The higher levels of MCP-1, TGF-β2, and VEGF in eyes with PCD indicated a change in their intraocular inflammatory microenvironment, which possibly led to cataract progression.Lens thickness and TGF-β2 level are independent risk factors for PCD.